2010
DOI: 10.1590/s0034-737x2010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Época de semeadura do milho para a região de Sete Lagoas, MG, baseada na probabilidade de ocorrência de períodos secos e chuvosos

Abstract: Corn sowing time in Sete Lagoas region, Minas Gerais State, based on the probability of occurrence of dry and rainy spellsThe objective of this study was to determine the probability of dry and rainy occurrence periods in Sete Lagoas, Minas Gerais State, Brazil, from a historical series of 66-year-long daily rainfall data to establish the best sowing date for corn crop. Dry days were considered as those that had precipitation below corn evapotranspiration, ET corn . This study was carried out for the stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
(3 reference statements)
0
5
0
4
Order By: Relevance
“…O atraso da semeadura na safrinha do Tocantins reduz a quantidade de chuvas disponível durante o ciclo da cultura, o que resulta em decréscimo do potencial produtivo. As fases mais críticas das plantas de milho como relação à exigência hídrica se concentram na emergência, no florescimento e no enchimento dos grãos (Silva et al, 2010 …”
Section: Resultsunclassified
“…O atraso da semeadura na safrinha do Tocantins reduz a quantidade de chuvas disponível durante o ciclo da cultura, o que resulta em decréscimo do potencial produtivo. As fases mais críticas das plantas de milho como relação à exigência hídrica se concentram na emergência, no florescimento e no enchimento dos grãos (Silva et al, 2010 …”
Section: Resultsunclassified
“…The maximum temperature obtained in the sowing periods varied from 28.4 to 33.1 °C, and the minimum temperature from 21.6 to 23.5 °C (Figures 1 and 2). Silva et al (2010), also found that the most critical phases of corn plants, concerning water requirements, are concentrated on emergence, flowering, and grain filling. As stated by these authors, periods of water shortages of one week, in the bolting phase, may reduce grain production by up to 50%, whereas under the same conditions, water deficiency after the beginning of grain formation may cause losses between 25 and 37%.…”
Section: Resultados E Discussõesmentioning
confidence: 94%
“…Vários trabalhos demonstraram que o milho pode ser cultivado no Brasil em diferentes épocas de semeadura (SILVA et al, 2010;UATE et al, 2015;COSTA et al, 2017), como no início do período chuvoso para a região, de setembro a novembro, conhecido como safra e, no final do período chuvoso para a região, nos meses de fevereiro e março, conhecido como safrinha. Entretanto, para o estado do Amazonas tem-se poucas informações sobre o efeito das épocas de semeadura para o cultivo de milho.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Posteriormente, utilizou-se a Cadeia de Markov de 1°ordem, por meio do aplicativo Instat Climatic (Stern et al, 2006), para se determinar as probabilidades condicionais de ocorrência de dias secos e chuvosos. Assim, os dias secos e chuvosos foram divididos em quatro subgrupos: a) dia seco com o dia anterior seco (SS), b) dia seco com o dia anterior chuvoso (SC), c) dia chuvoso com o dia anterior chuvoso (CC) e d) dia chuvoso com o dia anterior seco (CS) (Keller Filho et al, 2006;Silva et al, 2010;Moura et al, 2015). Cada ano (Q i ) pode ser descrito com uma sequência de dias secos (x j = 0) ou chuvosos (…”
Section: Methodsunclassified